Unveiling the Role of Local Cultural Considerations in Judicial Discretion: An Analysis of Inheritance Decisions in the Religious Courts of South Kalimantan - Zaidah, Yusna; Al-Amruzi, A. Fahmi; Sarmadi, A. Sukris (Al-Risalah, 2023)
In Religious Courts, numerous cases within the sphere of absolute authority are not exclusively fortified by material legal sources through legislation. The ingenuity of judges becomes indispensable in extracting the essence of the law from various sources, including the rich tapestry of local cultural customs inherent within the community. The concept also leads to the emergence of cases decided through the discretionary methods employed by judges. Therefore, this study aimed to discuss the local cultural forms that served as points of reference for judges when exercising their discretion in rendering verdicts on inheritance disputes within the Religious Courts of South Kalimantan. The existence of judicial discretion in the decision-making process was unravelled, particularly when legal considerations aligned with the mandates of the heirs, emanating from the local culture of the Banjar people residing in the region. Furthermore, the translation of the heir's mandate, resembling a testament, exemplified the exercise of unrestrained discretion by the judges. Local culture was viewed as an indispensable component of the living law that pervaded society, with its ability to adapt and engage with the ever-changing landscape.